2006
DOI: 10.1590/s0047-20852006000300003
|View full text |Cite
|
Sign up to set email alerts
|

Crime, diagnóstico psiquiátrico e perfil da vítima: um estudo com a população de uma casa de custódia do estado de São Paulo

Abstract: ResumoObjetivo: Estudar a população de uma casa de custódia quanto a aspectos criminais, diagnóstico clínico e perfil da vítima. Métodos: Foram examinados os prontuários de 269 pacientes durante o ano de 2005. Considerou-se apenas a população do gênero masculino cujos casos já tinham laudo anexado ao prontuário psiquiátrico-criminal. Resultados: Foi encontrado predomínio de transtornos psicóticos (58%). O crime mais freqüente foi contra a vida (52,8%), sendo o grupo dos pacientes psicóticos o que teve maior as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
5
0
4
Order By: Relevance
“…One of the latest prison studies, conducted in Brazil (Pondé, Caron, Mendonça, Freire, & Moreau, 2014), found no association between psychosis and the most serious crimes. That non-association is contrary to what another study found in a prison psychiatric ward, also in Brazil (Teixeira & Dalgalarrondo, 2006). In a prospective, longitudinal study of prison inmates in the United Kingdom, Keers, Ullrich, DeStavola, and Coid (2014) concluded that only an untreated schizophrenia diagnosis was significantly associated with violence.…”
mentioning
confidence: 64%
“…One of the latest prison studies, conducted in Brazil (Pondé, Caron, Mendonça, Freire, & Moreau, 2014), found no association between psychosis and the most serious crimes. That non-association is contrary to what another study found in a prison psychiatric ward, also in Brazil (Teixeira & Dalgalarrondo, 2006). In a prospective, longitudinal study of prison inmates in the United Kingdom, Keers, Ullrich, DeStavola, and Coid (2014) concluded that only an untreated schizophrenia diagnosis was significantly associated with violence.…”
mentioning
confidence: 64%
“…According to researchers, subjects with less severe mental retardation are more likely to commit the type of crimes that require greater planning. On the other hand, individuals with more severe retardation tend to commit sex offenses or crimes that need less planning 1,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study population, a predominance of psychotic disorder was found, with 44% of subjects presenting comorbidity with the use of drugs. Homicide was found to be the most frequently committed crime and the most strongly associated with psychotic patients, while sexual crimes were associated with mentally retarded patients 11 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Conseqüentemente, os instrumentos foram selecionados, sempre que possível, quando tinham sido submetidos a estudos de validação e de confiabilidade. Foram utilizadas as escalas MMDAS 20,21,26 , MINI 27 (entrevista neuropsiquiátrica miniinternacional) e a PANSS 8 (escala das sín-dromes positiva e negativa). Embora o MMDAS não tenha sido validado inteiramente no Brasil, após a tradução para o português realizada pelos autores deste artigo, a retradução para o inglês foi conduzida por um psiquiatra americano formado nos Estados Unidos e com grande experiência em psiquiatria clínica no Brasil (Dr. Sílvio Saidemberg).…”
Section: Artigo Originalunclassified